MAN AND TIGER RELATIONSHIPS IN CONTEMPORARY INDONESIAN LITERATURE - Rawson, David (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2024)
Media reports on recent attacks by Sumatran tigers in February and March 2024 have framed the man-tiger relationship as being one of conflict. Implicit in this reporting are on the one hand, the threat to the villagers who live proximate to parks and on the other hand, preserving an endangered animal. It has led to officials paradoxically setting traps for tigers in the sanctuary set aside for its preservation. Putu Fajar Arcana (2024), in reference to this conflict examines this relationship from different perspectives. He observes that man’s relationship with the tiger has been shaped by earlier belief systems; one that has venerated the tiger. He observes this tiger-man relationship in literary works which portray man’s tiger-like savagery and moral baseness and the tiger also seeking revenge against humans. To date little research has been undertaken on this man and tiger representation in contemporary Indonesian literature. This research has a compelling context, the Sumatran tigers is a critically endangered animal. The aim of this paper is to examines the representation of the tiger-man relationship in contemporary Indonesian literature over the New Order and post-New Order periods. It draws on the theory of narratology and selects literary works (short stories) from the New Order period and post-New Order periods. It examines the man and tiger relationship from the perspectives of beliefs, economic development and the environment over two political periods: the New Order and post-New Order periods. It finds that in literary works man’s economic activities depict a subjugation of myths and beliefs shaping values of respect and conservation of the tiger and its habitat.